Two-Dimensional Harmonic Retrieval in Correlative Noise Based on Genetic Algorithm. (7th July 2010) - Wu Wu, Sun-Yong Sun-Yong; Liao Liao, Gui-Sheng Gui-Sheng; Yang Yang, Zhi-Wei Zhi-Wei
Abstract : We propose a niche Genetic algorithm (GA) for the two-dimensional (2D) harmonic retrieval in the presence of correlative zero-mean, multiplicative, and additive noise. Firstly, we introduce a 2D fourth-order time-average moment spectrum which has extremum values at the harmonic frequencies. On this basis, the problem of harmonic retrieval is treated as a problem of finding the extremum values for which the niche GA is resorted. Utilizing the global searching ability of the GA, this method can improve the frequency estimation performance. The effectiveness of the proposed algorithm is demonstrated through computer simulations.